Effective Health Screening Strategies for Overcoming Non-Communicable Diseases in Sambimulyo Village, Banyuwangi Regency - Tazkia Izzatun Az Zahra; Era Samudra Hambin; Tsabitah Virza Novirianingtyas; Tri Yoga Wicaksono; Lailia Wahyuliana; Aulia Seftya Wardhani; Kayla Juwita Qalbu Latifa; Rafi Amrullah; Putri Fatimahtuz Zahra Puji Anggar Wati; Ayik Mirayanti Mandagi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Non-communicable diseases (NCDs) are chronic conditions that cannot be transmitted from one person to another. These conditions do not usually cause symptoms at first, but over time they can progress and damage the affected organ, leading to complications or even death. A lack of public knowledge about NCDs is a major contributor to complications and deaths from these diseases. To address this issue, a series of activities have been organized as part of the Movement for the Control of Non-Communicable Diseases. These activities focus on understanding the definitions, risk factors, prevention methods, and symptoms of diabetes, hypertension, and hyperuricemia. This study used a descriptive observational method, collecting primary data from pre- and post-test responses and health test results. In the first intervention, information about NCDs was provided and participants’ knowledge was increased by 31.25%. The second intervention was a health screening, which included measuring blood pressure and blood sugar levels. Uric acid levels were also measured at five points in Sambimulyo Village, with 129 participants. The results showed that 41.1% had high blood pressure, 29.5% were classified as diabetic, and 18.8% had high uric acid levels. These activities increased public knowledge about NCDs, provided information about the community’s risk factors, and improved communication, education, and information about how to manage these conditions.